2015
DOI: 10.1158/2326-6066.cir-15-0052
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Peptide Vaccine-Induced CD8 T Cells Strongly Modulate Intratumoral Macrophages Required for Tumor Regression

Abstract: Abundant macrophage infiltration of solid cancers commonly correlates with poor prognosis. Tumor-promoting functions of macrophages include angiogenesis, metastasis formation, and suppression of Th1-type immune responses. Here, we show that successful treatment of cervical carcinoma in mouse models with synthetic long peptide (SLP) vaccines induced influx of cytokineproducing CD8 T cells that strongly altered the numbers and phenotype of intratumoral macrophages. On the basis of the expression of CD11b, CD11c,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 45 publications
6
74
0
Order By: Relevance
“…The increasing reports on the immune modulatory properties of chemotherapy and radiotherapy, the debate on the exact working mechanism of CTLA-4-blocking antibodies [121][122][123] and the unexpected outcomes of myeloid cell depletion by CSF1R inhibition during immunotherapy [58,124] exemplify the need for immunomonitoring studies that analyze the effect of drugs on the immune system, and in particular beyond the expected mechanisms of action. This immunological knowledge then can be used to guide the rational design of combination therapies, which in the past were more based on empirical testing [23,95].…”
Section: Immunoguiding Is Important For the Development Of Immunothermentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing reports on the immune modulatory properties of chemotherapy and radiotherapy, the debate on the exact working mechanism of CTLA-4-blocking antibodies [121][122][123] and the unexpected outcomes of myeloid cell depletion by CSF1R inhibition during immunotherapy [58,124] exemplify the need for immunomonitoring studies that analyze the effect of drugs on the immune system, and in particular beyond the expected mechanisms of action. This immunological knowledge then can be used to guide the rational design of combination therapies, which in the past were more based on empirical testing [23,95].…”
Section: Immunoguiding Is Important For the Development Of Immunothermentioning
confidence: 99%
“…Chemotherapeutic agents may affect different immune cell populations and this effect may be transient [48]. While its seems logical to understand the dynamics and immune modulating properties of chemotherapeutic compounds, this is also required for other compounds such as targeted therapy of macrophages [58,124] and antibodies targeting costimulatory and coinhibitory molecules. This is well illustrated by different timing schedules of anti-CTLA-4 and anti-OX40 in a murine colorectal carcinoma model in combination with radiation therapy [130].…”
Section: Expert Opinionmentioning
confidence: 99%
“…16,18,19 Administration of CSF1/CSF1R inhibitors (monoclonal antibodies or small molecule inhibitors) to inhibit M2 macrophages and MDSCs was shown not only to be effective as a cancer monotherapy, but also as an adjuvant therapy to overcome resistance to therapeutic approaches like vaccination, chemotherapy, adoptive cellular therapy, radiotherapy and T cell checkpoint blockade. [20][21][22][23][24][25][26][27][28] Among the CSF1R inhibitors, PLX3397 is an effective small molecule receptor tyrosine kinase inhibitor for KIT/CSF1R/ FLT3 that is currently being trialled as a single agent or in combination therapy for patients with glioblastoma, breast cancer, melanoma, and other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that the abundance of DCs and the frequency and phenotype of macrophages changes concordant with CD8 + T cell activation. It has previously been reported that macrophages are modulated by the activity of CD8 + T cells and required for the antitumor response against TC-1 tumors elicited by vaccination (24). As such, it seems likely that the DC and macrophage dynamics in the stable disease and relapse phases are consequent to reduced recruitment of activated CD8 + T cells.…”
Section: Np-conjugation Improves Long Peptide Vaccination In Differenmentioning
confidence: 99%
“…To test this hypothesis, the E7 43-77 SLP (E7LP) (24) was conjugated to NPs, and compared to the non NP-conjugated free (liquid) E7LP in several mouse models of HPV + cancers. We comparatively evaluated efficacy of the two vaccine formulations in mice bearing tumors derived from inoculating HPV16 E6/7-transformed TC-1 cells, which have been widely used to test therapeutic strategies against HPV + cancers (24-28), and a new squamous cell carcinoma cell line (termed SC1) derived from a skin tumors in an HPV16 transgenic mouse (29,30).…”
Section: Introductionmentioning
confidence: 99%